Regionalizing the infrastructure turn: a research agenda. Issue 1 (1st January 2020) - Addie, Jean-Paul D.; Glass, Michael R.; Nelles, Jen
ABSTRACT: An interdisciplinary 'infrastructure turn' has emerged over the past 20 years that disputes the concept of urban infrastructure as a staid or neutral set of physical artefacts. Responding to the increased conceptual, geographical and political importance of infrastructure – and endemic issues of access, expertise and governance that the varied provision of infrastructures can cause – this intervention asserts the significance of applying a regional perspective to the infrastructure turn. This paper forwards a critical research agenda for the study of 'infrastructural regionalisms' to interrogate: (1) how we study and produce knowledge about infrastructure; (2) how infrastructure is governed across or constrained by jurisdictional boundaries; (3) who drives the construction of regional infrastructural imaginaries; and (4) how individuals and communities differentially experience regional space through infrastructure. Analysing regions through infrastructure provides a novel perspective on the regional question and consequently offers a framework to understand better the implications of the current infrastructure moment for regional spaces worldwide.